Costos de producción de la pitahaya en la finca Procel del cantón Palora de la provincia de Morona Santiago trimestre enero- marzo 2022. - Barba Lozano, Nancy Morella (2023)
The integrative project was carried out at the Procel Farm where yellow pitahaya is produced and marketed, one of the problems is that they do not have cost accounting, which causes ignorance of the cost of production of the fruit. The objective of this project is to determine the production costs of Pitahaya in the Procel Farm in the Palora Canton of the Province of Morona Santiago in the quarter of January - March 2022. The methodology used is a quantitative approach, descriptive, documentary, and field research type; techniques such as the interview that was applied to the manager, head of the production, accountant, and warehouseman and a survey for workers were used, which provided information on production costs, result listing in the cost of production of pitahaya empirically of $ 2.79 per kg with a profitability margin of 40%; Through bibliographic information, the production order cost system was implemented, since it is the most adaptable according to the activities of the farm. The production order cost system was designed for the period January - March 2022, raw material, labor, and indirect manufacturing costs were recorded in the cost sheet, obtaining real calculations of pitahaya production with a value of $3.16 per kg with a profitability margin of 60%.